An adaptation breeding strategy for water deficit in bean developed with the application of DSSAT3 drybean model - Wortmann, Charles S. (1998)
Bean (Phaseolus vulgaris L.) productivity is much constrained by water deficits in many production areas in eastern and southern Africa. The DSSAT 3 Drybean model was used to analyze the effects of water deficits on bean using genetic coefficients of four cultivars including an early, determinate type and early, intermediate and late maturity indeterminate bush types. More than 2300 simulations were run using meteorological data from 19 locations. The late maturing ideotype gave highest yield in less stressful environments but its yield was the least stable. In more stressful environments, early maturing ideotypes had highest mean yield and their yield was most stable in all environments. Stress was most severe and frequent in the later stages of growth; stress affected yield most during pod formation and fill, less during the early reproductive stage and least during the vegetative stage. Elements of a possible strategy for improving adaptation to water deficits are discussed, and specific information for the application of such a strategy is given for three locations which appear suitable as primary screening sites.